2023
DOI: 10.3390/ijerph20043119
|View full text |Cite
|
Sign up to set email alerts
|

The Connection between Absorptive Capacity and Green Innovation: The Function of Board Capital and Environmental Regulation

Abstract: The stress of environmental regulations, sustainable development objectives, and global warming is becoming more prominent now. Most studies conclude that the industrial sector is largely at fault and under tremendous pressure to address these climate change issues. This study highlights the significance of green innovation to Chinese firms in mitigating these conservational challenges, and the study probes the association between green innovation and absorptive capacity. Additionally, board capital (the socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…[ 51 ] found that GAC impacts innovation performance and green organizational ambidexterity (exploration and exploitation learning). Similar to this [ 71 , 72 ], emphasize on the role of GAC on firm performance, and [ 73 , 74 , 75 ] present the role of GAC on innovation for companies. GAC has been viewed in this context as a crucial tool for boosting organizational innovation and overall performance.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 72%
See 1 more Smart Citation
“…[ 51 ] found that GAC impacts innovation performance and green organizational ambidexterity (exploration and exploitation learning). Similar to this [ 71 , 72 ], emphasize on the role of GAC on firm performance, and [ 73 , 74 , 75 ] present the role of GAC on innovation for companies. GAC has been viewed in this context as a crucial tool for boosting organizational innovation and overall performance.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 72%
“…For example [ 71 ], establishes the link between GAC and firm performance in electronics industry in Taiwan and [ 72 ] establishes on GAC and firm performance for manufacturing firms in China. Also, GAC is related to green innovation in hotels and restaurants in China [ 74 , 50 ], SMEs’ green innovation adoption in Egypt [ 73 ], green service innovation and green dynamic capabilities in the context of Brazilian universities [ 112 ]. Contrary to the aforementioned studies, a study by Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the concept of green logistics will help policy makers and researchers to understand the importance of green logistics, to improve society and the economy of the countries, as well as their environmental efficiency [60]. A study on environmental regulations and laws encouraged several companies to look for new methods of reducing expenditure and costs, and brought positive results for green innovation [61]. Another study on green innovation for environmental operations led to improvements in the organization's operation, while the result also indicated that the executives would work towards environmental innovation, encouraging changes at an organizational level which led to utilizing environmentally friendly practices [9].…”
Section: Social Reputation For Environmental Concernmentioning
confidence: 99%
“…Second, the digital economy has increased the use and development of intelligent technologies such as artificial intelligence, cloud computing and the Internet of Things, optimizing the use of resources, lowering the cost of growth, and increasing the efficiency of energy use and city operations, thereby increasing GTFP [38,39]. In addition, the digital economy itself is constantly innovating to promote green technologies, for example, by promoting renewable energy innovations to reduce carbon emissions, production technology innovations to reduce the demand for finite resources, and green finance innovations to increase investment in sustainability and finance green total factor productivity [40]. Therefore, this paper proposes that the digital economy promotes GTFO through green innovation.…”
Section: Digital Economic Indexmentioning
confidence: 99%